UKURAN PERUSAHAAN SEBAGAI PEMODERASI PADA HUBUNGAN LIKUIDITAS, SOLVABILITAS, AKTIVITAS, DAN PROFITABILITAS TERHADAP PERTUMBUHAN LABA - Kristiana, Ida; Isnadia, Nova; Janie, Dyah Nirmala Arum (Jurnal Akuntansi dan Bisnis, 2025)
This study empirically investigates the relationship between profit growth and liquidity, solvency, activity, and profitability using business size as a moderating variable. Food and beverage companies listed on the Indonesia Stock Exchange between 2019 and 2023 are the study's subjects; 24 companies, or 120 samples, were chosen for the study using the purposive sampling method in accordance with predefined criteria; Moderated Regression Analysis (MRA) was used to analyze the data in order to determine the effect of moderation on the company size variable. The Indonesia Stock Exchange's official website, www.idx.co.id, provided the study's data. Profit growth is positively and significantly impacted by liquidity, solvency, activity, and profitability, according to the study, and the relationship between these elements and profit growth is moderated by the size of the business.